S94 Biological markers of favourable prognosis and successful pleurodesis for malignant pleural effusion. (15th November 2016) - Psallidas, I; Kanellakis, N; Thezenas, ML; Charles, P; Corcoran, JP; Hallifax, R; Talwar, A; Pascuall, CC; Kessler, B; Rahman, NM
Abstract : Introduction and objectives: Malignant pleural effusion (MPE) is a rapidly rising healthcare burden and critically hampers the patients' survival and quality of life. Current treatments aim to symptoms' palliation and talc pleurodesis remains a standard therapeutic modality. There is relatively little high quality research data in prediction of patients' survival and successful pleurodesis. Therefore prognostic and therapeutic biomarkers are desperately needed. Aim: To identify and validate novel prognostic and therapeutic biomarkers in MPE. Methods: Clinical data and pleural fluids from MPE patients, prior to treatment have been prospectively collected for TIME2 trial. According to the trial database patients have been classified in two different groups: survival cohort (poor, n = 20/good, n = 14) and treatment outcome cohort (success, n = 15/failure, n = 11). Pleural fluids on enrolment were assessed with mass spectrometry profiling after depletion of the 12 most abundant proteins. Full protein profile analysed with R software and ELISA technique was performed for the validation of the results. Pathway analysis on samples performed with Ingenuity Pathway Analysis software. Results: With the use of mass spectrometry we identified 1, 154 proteins in the pleural fluid, 167 of which were statistical significant (two tailed T-Test, p < 0.05) between survival groups and 97 of which were statistically significant (two tailed T-Test, p < 0.05) between the pleurodesis groups. Analysis of the data (cross validated by 3 independent core bioinformatic groups) identified 10 survival and 3 pleurodesis biomarkers that were differentially expressed in the favourable prognosis and treatment success group respectively. Exploration of the mass spectrometry data identified pathways that were upregulated on patients with favourable survival that could be used for targeted therapies. Conclusions: Based on unique database survival and therapeutic biomarkers were identified that can potentially stratify patients' management. The results are currently validated on a different retrospective dataset (TIME1 trial) and with a prospective clinical trial (SIMPLE study).